The intergovernmental relations and their regulation in the context of decentralization of fiscal policy - George Abuselidze (E3S Web of Conferences, 2021)
The suspension of economic relations as a result of the global pandemic has severely affected the country's peripheries. Unequal development of territorial units and overcoming socio-economic problems is the biggest challenge of any country. To address these challenges, the country needs to mobilize large amounts of finance and make optimal allocations. Intergovernmental relations play an important role in the effective implementation of the transformation of the country's economic and political system. The aim of the paper is to study the characteristics of revenue mobilization and distribution between the levels of the fiscal system. There are developed some recommendations for improving inter-budgetary relations based on the experience of different countries. The recommendations proposed as a result of the research analysis can be used for both theoretical (for lecture) and practical (for legislative) purposes.
Keywords: 330